2009
DOI: 10.1007/s11133-009-9137-1
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence and Control: State Action Against the Civil Rights-Era Ku Klux Klan

Abstract: Models that purport to explain the interplay between dissidents and the state generally assert, either explicitly or implicitly, that the path from state interests to action to outcomes is a linear one. Using the case of the United Klans of America (UKA) in North Carolina, I argue that state efforts to exert social control upon a perceived threat are shaped by a range of internal and external contingencies. In particular, I undertake a comparative analysis of two state agencies to demonstrate how a particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…1989) with research on the repression of particular groups between events (e.g. Boykoff 2007a; Cunningham 2003, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…1989) with research on the repression of particular groups between events (e.g. Boykoff 2007a; Cunningham 2003, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Black newspapers provide an important balance and corrective to a vein of academic research studying protest events that has drawn almost entirely on mainstream media and social media for its view of Black protest. We show that mainstream sources reinforce the longstanding official practice of treating Black protest and Black communities as inherently dangerous (Cunningham 2003, Cunningham 2009, Cunningham 2022, Mian 2020) and episodes of police violence as unusual. By contrast, Black newspapers treat police violence as a systemic problem (Weitzer and Tuch 2002) that is the object of ongoing community struggle (Balfour 2023, Berger 2009, Florini 2012, Hall 2005, Jackson 2022, Jackson 2021, Moulton , Santoro 2015.…”
Section: Introduc�onmentioning
confidence: 52%
“…Black protesters are often labeled as more dangerous. White authorities have long treated Black protests and communities as inherently dangerous while treating even violent White supremacists as less dangerous (Castle 2020, Cunningham 2003, Cunningham 2009, Cunningham 2022, Mian 2020 Research using the Dynamics of Collective Action (DCA) dataset generally finds more reports of police presence when protesters are Black (Davenport, Soule and Armstrong 2011) with most of the difference due to tactical extremism or targeting the state, and especially when the issue is police brutality (Reynolds-Stenson 2017). Interestingly, (Beyerlein, Soule and Martin 2015:411) found that mainstream newspapers reported police presence at less than a third of the same protests that participants said had police present.…”
Section: News Media and The Percep�on Of Violence And Disrup�onmentioning
confidence: 99%
“…Local and central authorities respond differently to these protests (Cai, 2010), but the net effect is to reduce or eliminate protest. Demobilizing strategies include surveillance (Cunningham, 2007), ridicule and stigma (Cunningham, 2009;Stern and, O'Brien 2012), control parables (Stern and Hassid, 2012), and relational repression (Deng and O'Brien, 2013). Only in rare cases have protests cohered into social movements, spreading across regions, social classes, and occupations, and making political demands on central authorities.…”
Section: Activism and Anti-activismmentioning
confidence: 99%